A posztmodern ember és az Ószövetség világa - Simon, Zsolt; Vanderstein, Noémi (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The title of this publication is “The World of the Post-modem Man and the Old Testament”. Nowadays, it is not easy to live your life according to the teachings of the Old Testament, and to take the challenges of the post-modern world at the same time. Our aim is to introduce the aspects of the Biblical issues and the academic perspectives of the topic, too. We intend to show the process of becoming a Subject from the individual as the starting point. It is necessary to see that culture plays an important role in people’s lives, culture that we are born into. This culture is the basis for both of the human beings’ religion-beliefs and their opinion about the crucial steps of the world.